Omejitve pravice do odpovedi kreditne pogodbe - Zgaga, Matevž (Podjetje in delo, 2018)
Freedom of contract is a general principle of contract law. However, in practice, before the parties enter into a loan contract, they rarely negotiate its provisions. Banks' general terms and conditions prevail. These terms and conditions usually include early termination right for the benefit of the creditor. The author discusses the validity of exercising such a right from the perspective of general principles and compulsory law. Following the analysis of early termination right in German, Swiss and English law, the article analyses the Slovenian statutory regulation and court practice, concluding with the author's position on some open issues.
Keywords: bančništvo; kazenskopravno varstvo; kreditne pogodbe; načelo vestnosti in poštenja; odpoved pogodbe; splošni pogodbeni pogoji; Zakon o potrošniških kreditih